Peningkatan Kompetensi Santri Pondok Pesantren melalui Workshop Life Skills Bidang Jaringan Komputer - Hendrik Kusbandono; Tri Lestariningsih; MH. Ramdhani Ismar; Mochamat Bayu Aji; Tri Septianto (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2023)
Salaf-based boarding schools still adhere to a traditional system in which they only teach religious sciences, and have not implemented skills-based education. Skills-based education is one of the important agendas in Islamic boarding schools, not only organizationally important but also students are equipped with life skills. In fact, not all boarding schools have explored skills education outside of religious education. The purpose of this PkM program is to provide workshops to improve competence to boarding school students in the form of skills. The methods used in this PkM program are interviews, observations, and the process of implementing the PkM program. The results of the PkM activities are in the form of the implementation of workshop activities starting from registration and attendance, opening, continuing with the introduction of IT and its implementation, IT life skills and computer network competencies, computer network installation, and closing. By providing workshop solutions to boarding school students in the form of skills, they will gain knowledge, skills, and expertise in the field of computer networks.